1996
DOI: 10.1021/ma951152v
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Ethylene−Styrene Copolymerization with a Methylaluminoxane-Free Half-Titanocene Catalyst

Abstract: Copolymerization of ethylene and styrene in the presence of the catalytic system η5-C5Me5Ti(CH2Ph)3−B(C6F5)3 has been investigated. Independently from the feed composition, basically alternating ethylene−styrene copolymers are obtained, together with some polyethylene and syndiotactic polystyrene, from which the former can be separated by solvent extraction. NMR analysis of suitably 13C-enriched end groups shows that the regiospecificity of styrene insertion in the initiation step is largely secondary. A tenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 22 publications
6
88
2
Order By: Relevance
“…4) give the values of 9 and 0.04, respectively. The value of r E ϫ r S Ϸ 0.4 reflects the alternating comonomers incorporation being in accord with data by Kakugo et al, 13 Zambelli et al, 31 and Oliva et al 42,43 reported for E/S copolymerization catalyzed with MAO-treated mono-Cp titanium complexes and ansazirconocenes. Contradictory, random comonomer incorporation catalyzed with MAO-treated chelatelike titanium complexes was communicated elsewhere.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…4) give the values of 9 and 0.04, respectively. The value of r E ϫ r S Ϸ 0.4 reflects the alternating comonomers incorporation being in accord with data by Kakugo et al, 13 Zambelli et al, 31 and Oliva et al 42,43 reported for E/S copolymerization catalyzed with MAO-treated mono-Cp titanium complexes and ansazirconocenes. Contradictory, random comonomer incorporation catalyzed with MAO-treated chelatelike titanium complexes was communicated elsewhere.…”
Section: Resultssupporting
confidence: 91%
“…Hence, half-sandwich titanium catalysts (producing sPS) in E/S feed gave rise to a number of products (such as polyethylenes (PE), sPS, and alternating E/S copolymers) that are dependent on polymerization conditions. 14,31 Common behavior was observed for chelatelike titanium complexes, 29,30 binuclear half-sandwich, and biscyclopentadienyll derivatives. 32 Thus, active sites originated under action of cocatalysts (MAO, perfluorophenyl borane, or borates) on mono-Cp titanium complexes, producing sPS, were Ti(III) species.…”
Section: Introductionmentioning
confidence: 95%
“…Half-titanocenes, such as Cp*TiF 3 , Cp*Ti(OMe) 3 and (indenyl)TiCl 3 , are efficient catalyst precursors for syndiospecific styrene polymerization [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]; however, these catalyst precursors showed low activities in the copolymerization, and the resultant polymers were a mixture of polyethylene (PE), syndiotactic polystyrene (SPS) and the copolymer (E-S) [41][42][43][44][45]. As related examples, Cp*TiMe 3 exhibited catalytic activities for both ethylene polymerization and styrene polymerization in the presence of MAO or B(C 6 F 5 ) 3 , and the resultant polystyrene possessed both atactic (via a cationic mechanism) and syndiotactic (via a coordination insertion mechanism) stereoregularity; the ratios were dependent upon the polymerization temperature [46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…One involves the syndiotactic copolymerization of styrene with a second monomer, particularly ethylene, to produce a styrene/olefin copolymer. 27,28 Another modification procedure involves the preparation of functionalized sPS polymers, such as sulfonated sPS, 29 acetylated sPS 30 and maleic anhydride-grafted sPS. 31 In addition, polymer blends also provide a way to modify sPS.…”
Section: Introductionmentioning
confidence: 99%